Emotion and Altruism: The Psychological Foundations of Community Mental Health Responses - Widyanti, Eka (Indonesian Scientific Publication, 2025)
This narrative review investigates the intersection of psychological, emotional, and contextual determinants in prosocial behavior and moral decision-making within mental health frameworks. The study aims to synthesize current empirical and comparative findings on how variables such as empathy, guilt, social norms, and cultural settings shape individual responses in social contexts. The review employed a rigorous literature search across four major academic databases—PubMed, Scopus, Web of Science, and Google Scholar—using Boolean combinations of keywords including